Oral Hygiene Practices And Teeth Cleaning Techniques: A Comprehensive Review (Journal of Namibian Studies : History Politics Culture, 2022)
Maintaining optimal oral hygiene is crucial for preventing dental diseases and promoting overall health. This comprehensive review aims to explore the current knowledge and practices related to oral hygiene and teeth cleaning techniques. The review will cover the importance of oral hygiene, the effectiveness of various teeth cleaning methods, and the factors influencing oral hygiene behaviors. The literature search will be conducted using multiple electronic databases, focusing on studies published in the last two decades. The findings will provide insights into the best practices for maintaining oral health and identify areas for future research and interventions. By synthesizing the current evidence, this review will contribute to the development of evidence-based recommendations for oral hygiene practices and inform strategies for promoting oral health at the individual and population levels.